2013
DOI: 10.1021/ja405108p
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Activation of the p53 Tumor Suppressor Pathway by an Engineered Cyclotide

Abstract: The overexpression of Hdm2 and HdmX is a common mechanism used by many tumor cells to inactive the p53 tumor suppressor pathway promoting cell survival. Targeting Hdm2 and HdmX has emerged as a validated therapeutic strategy for treating cancers with wild-type p53. Small linear peptides mimicking the N-terminal fragment of p53 have been shown to be potent Hdm2/HdmX antagonists. The potential therapeutic use of these peptides, however, is limited by their poor stability and bioavailability. Here, we report the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
316
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(321 citation statements)
references
References 47 publications
2
316
1
2
Order By: Relevance
“…This observation is consistent with recent studies which demonstrated that grafting sequences as long as sixteen amino acid residues into loop 6 does not alter the disulfide bond connectivity within MCoTI [29]. Moreover, the MCoTI-ll scaffold has been engineered to bind to a range of protein targets including HMD2 [29], beta-tryptase, human leukocyte elastase and matriptase [16,27,30,31], suggesting that the framework itself has plasticity to accommodate different sequences. However, introducing the Sortase A recognition sequence into other loop regions within the framework might pose a problem and hence would need to be carefully assessed on a case-by-case basis.…”
Section: Resultssupporting
confidence: 89%
“…This observation is consistent with recent studies which demonstrated that grafting sequences as long as sixteen amino acid residues into loop 6 does not alter the disulfide bond connectivity within MCoTI [29]. Moreover, the MCoTI-ll scaffold has been engineered to bind to a range of protein targets including HMD2 [29], beta-tryptase, human leukocyte elastase and matriptase [16,27,30,31], suggesting that the framework itself has plasticity to accommodate different sequences. However, introducing the Sortase A recognition sequence into other loop regions within the framework might pose a problem and hence would need to be carefully assessed on a case-by-case basis.…”
Section: Resultssupporting
confidence: 89%
“…Both MCoTI-I and MCoTI-II are stable in human serum, with MCoTI-I reported to have a half-life of more than 2 days (10,11). The stability of cyclotides, coupled with their high sequence diversity, has led to the suggestion they might be useful in the design of novel drug leads (12).…”
mentioning
confidence: 99%
“…Proof-of-concept for such work was recently demonstrated when a grafted cyclotide, showed activity against growth factors involved in angiogenesis [101]; it is well-established that tumor growth is usually associated with unregulated angiogenesis [102]. As further proof-of-concept, more recently, work, which was patented [103], demonstrated that engineered cyclotides were cytotoxic to cancer cells through activation of the p53 tumor suppressor pathway, which is commonly inactivated by these cells to promote survival [104].…”
Section: Discussionmentioning
confidence: 99%